(untitled) (Research, Society and Development, 2022)
Amazonas has the highest incidence rate of tuberculosis in the country with 64.8 cases per 100,000 inhabitants in 2020. From January to February 2021, 370 cases were recorded in the state, with 270 notifications in Manaus. The indicators are monitored by the FVS-AM State Tuberculosis Control Program (PECT/FVS-AM, 2021). The general objective of this study was to investigate the challenges, aspects and treatments associated with tuberculosis control in Manaus-AM. Specific objectives: to describe the general aspects of tuberculosis; to analyze the symptoms of TB in the last decade; advances in the treatment of tuberculosis; classify the challenges in completing treatment from the diagnosis of the disease; show the challenges related to the treatment and control of tuberculosis in Manaus-AM. It was a study that was carried out through a systematic review, based on data sources from qualitative bibliographic research. The study was carried out through research on academic websites: Google academic, Scielo and the collection of the sectoral library of the Faculdade Metropolitana de Manaus- FAMETRO. Manaus is the most populous city in the northern region of Brazil and has the highest TB incidence and mortality rate. The city concentrates almost 90% of hospitalizations of patients with TB in the state. The study presented is relevant because it is a topic that can contribute to the understanding of TB treatment and diagnosis, which is the cause of thousands of deaths every year in the world.